HUBUNGAN KOMPETENSI KEPRIBADIAN GURU DENGAN MOTIVASI BELAJAR SISWA DI SDI TIMUNG TAHUN 2021 - Fabianus Hadiman Bosco; Mikael Nardi; Bernadeta Mulia (JIPD (Jurnal Inovasi Pendidikan Dasar), 2022)
This research is motivated by students sometimes not doing the assignments given by the teacher, students not being active in learning activities, students being lazy to take part in teaching and learning activities in class, students not being able to read, there are still students who play and disturb their friends while they are studying. In learning, teachers tend to focus on students who have good abilities, and teachers often ignore students who have less abilities. This study aims to determine whether there is a relationship between the teacher's personality competence and student learning motivation.This type of research is quantitative. The population of this study were all teachers and students at SDI Timung and the research sample was teachers at SDI Timung totaling 11 people and students totaling 50 people. Data collection techniques in this study using a questionnaire. This questionnaire was given to 50 students to assess the teacher's personality competence which consisted of 20 statements and student learning motivation was given to the students themselves which consisted of 20 statements. The results of the study obtained rcount = 0.71 while the value of rtable = 0.284. The significance of the relationship between teacher personality competence and student learning motivation is shown by rcount greater than rtable at degrees of freedom (dk) = 48 and alpha 5%, namely rcount 0.71>rtable = 0.284. This shows that there is a positive relationship between teacher personality competence and student learning motivation and a high relationship because the r value is in the coefficient interval 0.60-0.799. The contribution or contribution of the teacher's personality competence variable to student learning motivation is shown in the coefficient of determination. The result of the analysis of the coefficient of determination is 50.41%. This means that the contribution or contribution of the teacher's personality competence variable (X) with student learning motivation (Y) is 50.41% and 49.59% is influenced by other factors not examined in this study. Thus, it can be concluded that there is a positive relationship between the teacher's personality competence and student learning motivation. Keywords: Competence, Teacher Personality, and Learning Motivation